KEBIJAKAN PENGELOLAAN AIR UNTUK MEWUJUDKAN KETAHANAN PANGAN - Maryadi Maryadi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Up until now, some countries still facing food shortage. One of thereasons is waters carcity. As we know, it is estimated that 70 percentof the water consumed worldwide, including that diverted from riversand pumped from underground, is used for irrigation, while some 20percent is used by industry and 10 percent for residential purposes. Inthe increasingly intense competition for water among these three sectors,the economics of water do not favor agriculture. In China, 1,000 tons ofwater can be used to produce 1 ton of wheat, worth perhaps 200, or toexpand industrial output by 14,000—70 times as much. In a countrythat is desperately seeking economic growth and the jobs it generates,the gain in diverting water from agriculture to industry is obvious.